On Multi-Criteria Decision Making problem via Bipolar Single-Valued Neutrosophic Settings - Mohana K; Christy V; Florentin Smarandache (Neutrosophic Sets and Systems, 2019)
In this paper, the idea bipolar single-valued neutrosophic (BSVN) set was introduced. We also introduce bipolar single-valued neutrosophic topological space and some of its properties were characterized. Comparing Bipolar single-valued neutrosophic sets with score function, certainty function and accuracy function .Bipolar single-valued neutrosophic weighted average operator (Aω) and bipolar single-valued neutrosophic weighted geometric operator (Gω) were developed and based on Bipolar single-valued neutrosophic set, a multiple decision making problem were evaluated through an example to select the desirable one.